The relationship between religiosity and oral health status as well as oral health-related quality of life (OHRQoL): Scoping review - Puspitasari, Ika Cahyani; Novrinda, Herry; Bahar, Armasastra; Rahardjo, Anton; Badruddin, Iwany Amalliah (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
ABSTRACTIntroduction: The World Health Organization (WHO) reported in 2022 that approximately 3.5 billion people worldwide suffer from oral diseases. Poor oral health not only leads to clinical problems but also results in social disadvantages and reduced quality of life. In health epidemiology, religion is considered a social determinant of health. Higher levels of religiosity are believed to contribute to better oral health through social support and psychological well-being. Religiosity functions as a psychosocial determinant of health that enhances emotional stability and preventive behaviors. Therefore, examining the relationship between religiosity and oral health status, as well as oral health-related quality of life (OHRQoL), is important as a basis for developing promotive and preventive interventions based on a bio-psycho-social-spiritual approach. Methods: A literature search was conducted in PubMed, ScienceDirect, EBSCOhost, and SpringerLink using the keywords “belief,” “religion,” “religiosity,” “oral health,” “quality of life,” and “oral health-related quality of life”. Manual searching was performed through the reference lists of relevant articles. This study employed a scoping review method based on the framework proposed by Arksey and O’Malley. Results: Five publications met the inclusion criteria. Three studies demonstrated a positive relationship between religiosity and OHRQoL, indicating better oral health status and lower mean DMFT scores. Two other studies reported negative associations: individuals without religious affiliation had better OHRQoL, and the prevalence of dental diseases among clergy and monastic communities was higher than that of the local population. Conclusion: Religiosity is associated with oral health status and OHRQoL, acting both as a protective and a risk factor. These findings emphasize the importance of considering spiritual aspects in planning community oral health programs. Practical implications include the integration of faith-based oral health education, behavioral counseling, and collaboration between health professionals and religious leaders.KEYWORDS: Religiosity, oral health status, oral health-related quality of life (OHRQoL)Hubungan antara religiusitas dan status kesehatan oral serta oral health related quality of life (OHRQoL): Scoping reviewABSTRAKPendahuluan: Laporan World Health Organization (WHO) tahun 2022 menyebutkan sekitar 3,5 miliar penduduk dunia mengalami penyakit gigi dan mulut. Kondisi kesehatan rongga mulut yang buruk tidak hanya berdampak klinis, tetapi juga menimbulkan kerugian sosial dan menurunkan kualitas hidup. Dalam epidemiologi kesehatan, agama dipandang sebagai determinan sosial kesehatan. Tingkat religiusitas yang tinggi diduga berkontribusi pada kesehatan oral melalui dukungan sosial dan kesejahteraan psikologis. Religiusitas berperan sebagai penentu kesehatan psiko-sosial yang meningkatkan stabilitas emosional dan perilaku preventif. Kajian hubungan religiusitas pemeluk agama dengan status kesehatan oral dan oral health related quality of life (OHRQoL) diperlukan sebagai dasar pengembangan intervensi promotif dan preventif berbasis pendekatan bio-psiko-sosial-spiritual. Metode: Pencarian literatur dilakukan pada PubMed, ScienceDirect, EBSCOhost, dan SpringerLink menggunakan kata kunci belief, religious, religions, oral health, life quality, dan oral health related quality of life. Penelusuran manual dilakukan melalui daftar referensi artikel relevan. Penelitian menggunakan metode scoping review menurut Arksey dan O’Malley. Hasil: Diperoleh lima publikasi yang memenuhi kriteria. Tiga penelitian menunjukkan hubungan positif antara religiusitas dengan OHRQoL, status kesehatan mulut lebih baik, serta rerata DMFT lebih rendah. Dua penelitian lainnya menunjukkan hubungan negatif: individu tanpa afiliasi agama memiliki OHRQoL lebih baik, dan prevalensi penyakit gigi pada komunitas pendeta dan biarawan lebih tinggi dibandingkan penduduk lokal. Simpulan: Terdapat hubungan antara religiusitas dan status kesehatan oral serta (OHRQoL) sebagai faktor protektif dan faktor resiko. Temuan ini menegaskan pentingnya mempertimbangkan aspek spiritual dalam perencanaan program kesehatan gigi masyarakat. Implikasi praktis mencakup integrasi edukasi kesehatan mulut berbasis komunitas keagamaan, konseling perilaku, serta kolaborasi antara tenaga kesehatan dan pemuka agama.KATA KUNCI: religiusitas, status kesehatan oral, kualitas hidup terkait kesehatan oral (OHRQoL)